Why Web-Conferencing Matters: Rescuing Education in the Time of COVID-19 Pandemic Crisis - Adipat, Surattana (Frontiers in Education, 2021)
Physical interaction between humans has steadily decreased over the past year as a result of the COVID-19 pandemic. As a result, the adoption of e-conferencing has seen a huge increase in conducting business globally and technologically mediated interactions are now the order of the day—the new normal. The virtualization of meetings promotes collaboration among colleagues, target markets, associates, teachers, and students working towards the organization’s objectives. Using web conferencing in learning meets the primary goal of both educators and students. It facilitates the creation of the best learning environment for students and aids in the realization of a balance between life and teaching duties for educators. Through web conferencing, higher learning institutions have the ability to capitalize on the available technologies to expand the access to instructors online while also creating new experiences in the teaching and learning environment. The elimination of the need to travel for students' field trips has also been realized due to technological advances, and virtual tours have replaced these trips. A descriptive approach is adopted for the study, and it relies on information from peer-reviewed journals. Drawing from the literature review, the study first identifies web-conferencing in various facets of education. Secondly, it discusses web-conferencing adoption and its influence on teaching and learning. Third, a discussion on the importance and benefits as well as disadvantages of web-conferencing is outlined. Fourth, the study exemplifies two web-conferencing platforms: Zoom and Google Meet. The study further discusses the future of adopting web-conferencing in education.